First Aspect of Conventional Power System Assessment for High Wind Power Plants Penetration - A Merzic; M. Music; M Rascic (International Journal of Renewable Energy Development, 2012)
Most power systems in underdeveloped and developing countries are based on conventional power plants, mainly "slow-response" thermal power plants and a certain number of hydro power plants; characterized by inflexible generating portfolios and traditionally designed to meet own electricity needs. Taking into account operational capabilities of conventional power systems, their development planning will face problems with integration of notable amounts of installed capacities in wind power plants (WPP). This is what highlights the purpose of this work and in that sense, here, possible variations of simulated output power from WPP in the 10 minute and hourly time interval, which need to be balanced, are investigated, presented and discussed. Comparative calculations for the amount of installed power in WPP that can be integrated into a certain power system, according to available secondary balancing power amounts, in case of concentrated and dispersed future WPP are given. The stated has been done using a part of the power system of Bosnia and Herzegovina. In the considered example, by planned geographically distributed WPP construction, even up to cca. 74% more in installed power of WPP can be integrated into the power system than in case of geographically concentrated WPP construction, for the same available amount of (secondary) balancing power. These calculations have shown a significant benefit of planned, geographically distributed WPP construction, as an important recommendation for the development planning of conventional power systems, with limited balancing options. Keywords: balancing reserves,  geographical dispersion, output power  variations